2022
DOI: 10.1002/iju5.12447
|View full text |Cite
|
Sign up to set email alerts
|

Castration‐resistant prostate cancer diagnosed during leuprorelin treatment for spinal and bulbar muscular atrophy

Abstract: Introduction We report a prostate cancer case diagnosed during leuprorelin treatment for spinal and bulbar muscular atrophy which is a X‐linked recessive, lower motor neuron disease. Case presentation A 64‐year‐old man who had received leuprorelin treatment over 3 years for his spinal and bulbar muscular atrophy presented with an enlarged prostate accompanied by abdominal pain and constipation. An abnormally high serum prostate‐specific antigen of 17.7 ng/mL and a low (castration level) serum testosterone leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…5 As long-term ADT is currently in clinical use in Japan for patients with SBMA, the links between microsatellite expansion in AR, androgen deprivation, and prostate cancer requires investigation to optimally balance benefits and harms of such treatment strategies for patients. Maria Pennuto Ph.D. 1,2 , Monica Montopoli Ph.D. 2,3,4 and Carlo Rinaldi M.D, Ph.D. 5 1 Department of Biomedical Sciences, University of Padova, Italy, 2 Veneto Institute of Molecular Medicine (VIMM), Padova, Italy, 3 Department of Pharmaceutical and…”
Section: Editorial Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…5 As long-term ADT is currently in clinical use in Japan for patients with SBMA, the links between microsatellite expansion in AR, androgen deprivation, and prostate cancer requires investigation to optimally balance benefits and harms of such treatment strategies for patients. Maria Pennuto Ph.D. 1,2 , Monica Montopoli Ph.D. 2,3,4 and Carlo Rinaldi M.D, Ph.D. 5 1 Department of Biomedical Sciences, University of Padova, Italy, 2 Veneto Institute of Molecular Medicine (VIMM), Padova, Italy, 3 Department of Pharmaceutical and…”
Section: Editorial Commentmentioning
confidence: 99%
“…The case report from Atsushi et al . reignites a long‐standing debate whether the size of the CAG microsatellite expansion in the AR gene influences development and progression of prostate cancer, the second most prevalent malignancy in men worldwide 3 . It has been observed that the size of the CAG repeats inversely correlates with the AR transcriptional activity and the risk of developing prostate cancer, 4 therefore suggesting that SBMA patients are less at risk compared to the general population.…”
mentioning
confidence: 99%